Growing up: Hindu and Buddhist initiation rituals among Newar children in Bhaktapur, Nepal : with a film on DVD by Christian Bau - Gutschow, Niels; Michaels, Axel (Ethno-Indology, 2008)
The authors - an architectural historian (Niels Gutschow) and an indologist (Axel Michaels) - are presenting the second part of a trilogy of studies of life-cycle rituals in Nepal, carried out under the auspices of the Collaborative Research Centre “Dynamics of Ritual”. The initiation of boys and girls of both Hindus and Buddhists of the ethnic community of Newars in the Kathmandu Valley are documented. The first part of the book presents elements of Newar rituals, the spatial background of Bhaktapur and the hierarchy of ritual specialists - illustrated by 21 maps. The second part documents with detailed descriptions the. rst feeding of solid food, birthday rituals, and pre-puberty rituals like the first shaving of the hair, the boy’s initiation with the loincloth (in Buddhist and Hindu contexts), the girl’s marriage with the bel fruit and the girl’s seclusion. One girl’s marriage (Ihi) and three boy’s initiations (Kaytapuja) are documented on a DVD. The third part presents the textual tradition: local handbooks and manuals used by the Brahmin priest to guide the rituals. Two of these texts are edited and translated to demonstrate the function of such texts in a variety of contexts. The films, which were originally published on a DVD accompanying the book, are archived in the heidICON multimedia database and can be viewed via the following links: 1. Bel fruit and loincloth - initiations of boys and girls in Bhaktapur, Nepal https://doi.org/10.11588/heidicon/23793779 2. Bel-Frucht und Lendentuch - Initiationen von Mädchen und Jungen in Bhaktapur, Nepal https://doi.org/10.11588/heidicon/23793783